Optimal Capital Structure of PT. S2P For Project Extension Cilacap CFSPP Unit 3 Extension (1x600 MW) 2307 kcal/kwh at The Year of 2012 - Pratiwi, Yasmin Trianti (Journal of Business and Management, 2012)
In order to meet the electricity demand in Indonesia and rapid growth of the Company, PT.Sumber Segara Primadaya, a private company, wants to decide the best financing alternative for the Cilacap CFSPP Unit 3 Project Extension (1x600MW) at the super critical point of 2307 kcal/kWh at the year of 2012. Based on the feasibility study, the company requires some amount of fund, which can be acquired from the debt or the equity. However, the debt and equity proportion is very important for the return, because it is related to the cost of the financing; Weighted Average Cost of Capital (WACC). With the WACC method, the Company can determine the best financing alternative based on the lowest WACC. Furthermore, the result of the WACC approach will be compared with the financial projection of the Company when the project will start. Instead of using one method, the Company will also use the EPS (Earnings Per Share) approach as the comparing method. EPS method is a way to determined the best financing decision for the Company with considering the greatest Earnings Per Share in every debt-equity proportion level. The optimal financing alternative for this project is 50,60% of debt and 49,40% of equity. At this proportion level, the value of the Company also reach the highest point, USD 497.408.734. Based on the EPS method, the optimum debt level is 0% with the equity of 100%. The different result from both method can be occured because the EPS does not considering the cost of each financing decision. Overall, the WACC method are more preferred than the EPS method because EPS don’t calculate the financing cost of both equity and debt. The lowest financing cost will give the highest yield. Keywords : optimum capital structure, strategic financing decisions, WACC, earnings per share